Acyclovir Induced Acute Kidney Injury In Acute Meningitis Patient: A Case Report Highlights the Concurrence Of AKI Risk Factors And The Neutropenic Effect Of Ticlopidine - Amin, Arwa M.; Ibrahim, Baharudin; Sarriff, Azmi (International Organization of Scientific Resaerch (IOSR), 2014)
Nephrotoxicity is one of the challenging side effects of acyclovir use in clinical practice. The Concomitant use of other nephrotoxic antibiotics, in addition to patient's risk factors, can trigger acyclovir induced acute kidney injury (AKI). We described a case of acute meningitis in 68 year old female patient with underlying history of ischemic heart disease managed by ticlopidine. The gram stain, culture and PCR of the CSF did not show any positive growth of bacterial infection or HSV. However, the negative CSF gram stain and culture caused a confusion of the diagnosis of bacterial meningitis with viral meningitis. The patient had AKI induced by the treatment with acyclovir for 16 consecutive days and possibly triggered by other AKI risk factors. Hemodialysis and hydration did not reverse the kidney function to normal. However, it was reversed to its normal status only after the discontinuation of acyclovir. The neutropenic effect of ticlopidine can be a risk to the patient that could lead to fatal infection. In this case report we reviewed the literature on the nephrotoxicity of acyclovir, the neutropenia of ticlopidine and a proposed role of granulocyte colony stimulating factor (G-CSF).